Identifikasi E-Form (Elektronik Formulir) Identitas Pasien Rawat Jalan pada Aplikasi Eti Care di Rumah Sakit Budi Kemuliaan Jakarta - Dyah Melisa Setianingrum; Dina Sonia; Muhammad Fuad Iqbal; Daniel Happy Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
Building an effective and efficient health system is an important effort to improve the quality of health services in Indonesia, the implementation of RME is an integral component in the modern health service system. The government issued the One Healthy policy in efforts to implement Health Data governance. In order to achieve this, data variables and data formats/values ​​determined by the Ministry of Health must be used as a reference in the implementation of RME based on Minister of Health Regulation No. 24 of 2022. The aim of this research is to analyze data variables in the ETI Care application for outpatient registration at Budi Kemuliaan Hospital Jakarta according to the applicable guidelines, that is Minister of Health Decree Number HK.01.07/MENKES/1423/2022. This research uses descriptive qualitative methods. Data variables were obtained and their conformity with the existing meta data in the ETI Care application with government meta data, that is in the general identity there were 13 missing data variables and 2 variables that did not exist in the identity of the newborn baby, and 7 data variables that did not match the general identity and 1 data variable whose format/value did not match the identity of the newborn baby. It is necessary to develop the system by involving users in adjusting technical and organizational policies. There are still data variables that do not exist in the ETI Care application in the outpatient registration section, and there is also a discrepancy between the format/value of outpatient registration in the ETI Care application and the format/value of Minister of Health Decree Number HK.01.07/MENKES/1423/2022. This requires further communication with the vendor regarding system development in accordance with applicable guidelines.